2005
DOI: 10.1176/appi.ajp.162.1.162
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis in Patients With Schizophrenia

Abstract: The male patients with schizophrenia in this study suffered from low bone density. This finding as well as other reports lend support to directing more attention to bone metabolism in patients with schizophrenia, although there is no universally accepted screening policy to identify individuals at high risk for osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 31 publications
4
70
0
8
Order By: Relevance
“…Male patients with schizophrenia treated for at least 1 year with oral risperidone had normal markers of bone remodeling in more than 60% of patients, while BMD at the lumbar region was lower than in healthy subjects [41]. This is in contrast with Bergeman et al [42] who reported high bone turnover but normal BMD in young women with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Male patients with schizophrenia treated for at least 1 year with oral risperidone had normal markers of bone remodeling in more than 60% of patients, while BMD at the lumbar region was lower than in healthy subjects [41]. This is in contrast with Bergeman et al [42] who reported high bone turnover but normal BMD in young women with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies examined only small samples (range 10-402 patients), thirteen studies published between 1980 and 2005 consistently found decreased bone mineral density (osteoporosis) of people with schizophrenia compared to normal controls (69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82). One reason for this finding is that many antipsychotic drugs increase prolactin levels.…”
Section: Musculoskeletal Diseases (316 Medline Hits)mentioning
confidence: 99%
“…It is thought that time of onset of schizophrenia can be 5 years earlier in men than women (32). For this reason, exposure to factors related with schizophrenia and which may affect bone mineral density is longer for male patients (16). In our study, although it was found that gender has no effect on bone mineral density, low number of patients and not exactly knowing ages of disease onset in our patient group can be interpreted as limitations of our study.…”
Section: Discussionmentioning
confidence: 54%
“…There are several studies showing low bone mineral density in chronic schizophrenia patients (14,16,22). Polydypsia (23), neuroleptic use and related hyperprolactinemia (8,(24)(25)(26)(27)(28)(29), excessive smoking (11), substance and alcohol dependence (6) and lack of mobility (30) are among risk factors of higher osteoporosis prevalence among psychiatric patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation